Development and partial validation of an RT-qPCR assay for the rapid detection of spring viremia of carp virus (SVCV) - Zhu, Peng; Sun, Jie; Liao, Lishan; Zuo, Zhiheng; Rice, Annabel; Gui, Shishun; Wu, Jiang; Zhu, Yumin; Zhang, Lei; Liu, Hongwei; Stone, David; Liu, Hong (Frontiers in Microbiology, 2026)
Spring viremia of carp (SVC), caused by spring viremia of carp virus (SVCV), is a highly contagious disease that poses a serious threat to cyprinid aquaculture and international trade, and it is listed as a notifiable disease by the World Organization for Animal Health (WOAH). Effective surveillance and control of SVCV rely on accurate and highly sensitive molecular diagnostic methods. However, several previously published RT–qPCR assays contain mismatches between primer/probe sequences and viral genomes, which may lead to false-negative results and reduced diagnostic reliability. In this study, a whole-genome comparison of 24 representative SVCV strains covering all four genotypes (SVCVa–d) was conducted, and a new primer–probe set (Cefas AR) targeting a highly conserved region of the L gene was designed. Reaction conditions were optimized, and the assay was rigorously validated in accordance with the WOAH Manual of Diagnostic Tests for Aquatic Animals. The developed RT–qPCR assay exhibited excellent analytical performance, with a limit of detection of 1.28 copies/μL, diagnostic sensitivities of 100% for cell-culture isolates and 96.6% for tissue samples, and a diagnostic specificity of 100%. In addition, the assay demonstrated strong reproducibility and consistency across nine independent laboratories. In conclusion, the WOAH-validated RT–qPCR assay developed in this study provides a highly sensitive, specific, and reliable tool for rapid screening, routine surveillance, and confirmatory diagnosis of SVCV, supporting sustainable aquaculture development and international aquatic animal health management.